Maritime ISAR imaging with airborne radar - Bäckström, Veronica; Skårbratt, Anton (My University, 2010)
Inverse synthetic aperture radar (ISAR) provides a way to produce high quality images of ships by use of their angular motion. This report addresses how this can be done and what possibilities, and difficulties, that are associated with the technique. Simulations have been conducted in Matlab consisting of 3D models of two ship types and their motion, as well as implementation of a signal processing algorithm for ISAR imaging. Various scenarios have been simulated to investigate the demands on performance to achieve images that can be used for identification. Results from these are presented for both full knowledge of the ship’s motion and for estimations when this knowledge is absent. The simulated ship motions seem to provide enough resolution to recognize major ship features and the most suitable coherent processing time was found to be around one second for larger ships. Simulations also showed that a direct Fourier processing of the collected signal gives promising results for identification purposes.
Keywords: Fysik; Physical Sciences